Perancangan Aplikasi E-KIRT Berbasis Android untuk Meningkatkan Pemasaran dan Penjualan bagi Kelompok Industri Rumah Tangga - Solikhin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
This study will produce a system of text-based information security applications using cryptography algorithms Hill Code and Steganography LSB (Least Significant Bit). System information security applications are built to be used for text-based data security. The algorithms used for cryptography is Hill Code with a matrix of 2 x 2sebagai encryption keys, whereas the description used for the inverse of a matrix initial key. Steganography algorithm used is the LSB (Least Significant Bit) insertion in every bit of content (confidential data) into a low bit or bits of the far right. As known to a bitmap (.bmp) 24 bits consist of three pixels in which each pixel is a collection of 8 bits or 1 byte (a value between 0 to 255atau in binary format between 00000000 to 11111111), who presented the value of the intensity of the light that forms the base color namely red, green or blue (red-green-Blue or RGB). Thus in each pixel can be inserted 3 content. The results of the implementation and testing of the system shows that the system is running well, the implementation of the algorithm results are consistent with the manual calculation.